Production of regenerated silkworm silk fibers from aqueous dopes through straining flow spinning. Issue 21 (November 2019) - Madurga, Rodrigo; Gañán-Calvo, Alfonso M; Mariscal, Triana; Plaza, Gustavo R; Guinea, Gustavo V; Elices, Manuel; Pérez-Rigueiro, José
The possibility of spinning regenerated silkworm ( Bombyx mori ) fibers from a range of aqueous dopes by using a biomimetic approach based on straining flow spinning is explored in this work. It is found that spinning conditions can be established that allow fibers to be produced from environmentally friendly dopes with fibroin concentrations even one order of magnitude lower than that of the natural system. However, it is also found that the spinning process is favored and that the mechanical properties of the fibers are improved when dopes with higher fibroin concentration are employed. Since highly concentrated fibroin solutions in water are unstable, a stabilizing agent is required in order to obtain a spinnable dope at such large protein concentrations. CaCl2 is found to be an adequate stabilizing agent compatible with the straining flow spinning process. The optimization of the spinning parameters leads to the production of high-performance fibers with a work to fracture comparable to that of the natural material.